The membrane potential and permeabilities of the L cell membrane to Na, K and chloride - Lamb, J. F. (1971)
1. The chloride content and fluxes, and the membrane potential of L cells have been measured. 2. L cells contain chloride, 70 m-mole/l. intracellular water and have a flux of 5·5 p-mole/cm(2) sec. 3. The membrane potential is -15 mV.K-free Krebs causes an increase in E(m) and replacing chloride with sulphate causes a temporary reduction in E(m). 4. These values for E(m) and chloride, and previously obtained values for Na and K fluxes and contents were used to calculate the permeabilities of the various ions using the Goldman constant field theory. This gave permeabilities of 6·3, 4·2 and 51 × 10(-9) cm/sec for K, Na and chloride respectively, a ratio of 1:0·67:8·10. 5. It is concluded that these cells have a low membrane potential because the P(K) is some 100 times lower than in skeletal muscle, therefore leading to a P(K) of the same order as P(Na).